2017
DOI: 10.1093/jxb/erx016
|View full text |Cite
|
Sign up to set email alerts
|

Non-SMC elements 1 and 3 are required for early embryo and seedling development in Arabidopsis

Abstract: HighlightAtNSE1 and AtNSE3 are crucial factors for early embryo and seedling development, and mutations of AtNSE1 and AtNSE3 can affect cell division and the DNA repair process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 93 publications
4
36
0
Order By: Relevance
“…This remained true even after switching the tag positions (N-and C-terminal positions) and extensive optimization (Supplemental Figure 8). Within the NSE1-NSE3-NSE4 subcomplex, we measured positive interactions of both NSE4 paralogs with NSE3 and confirmed (Li et al, 2017) the interaction of NSE1 with NSE3 ( Figure 7A). However, we did not detect interactions between (F) Meristem size estimation.…”
Section: Loss Of Nse4a Function Causes Upregulation Of Dna Damage Repsupporting
confidence: 70%
“…This remained true even after switching the tag positions (N-and C-terminal positions) and extensive optimization (Supplemental Figure 8). Within the NSE1-NSE3-NSE4 subcomplex, we measured positive interactions of both NSE4 paralogs with NSE3 and confirmed (Li et al, 2017) the interaction of NSE1 with NSE3 ( Figure 7A). However, we did not detect interactions between (F) Meristem size estimation.…”
Section: Loss Of Nse4a Function Causes Upregulation Of Dna Damage Repsupporting
confidence: 70%
“…Afterwards, the cleared ovules were observed and photographed under an Olympus FluoView FV1000 microscope (https://www.olympus-lifescience.com/). Endosperm free nuclei were observed through an ovule autofluorescent method as described (Li et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…For flow cytometry analysis, three or more samples were used with each sample containing at least 10 000 nuclei isolated from the primary roots of 5‐DAG seedlings. Isolation of nuclei and flow cytometry analysis were performed with a Beckman flow cytometer according to a reported method (Li et al ., ). The endoreplication index (EI) was calculated using the following equation: EI = (0 × %2C) + (1 × %4C) + (2 × %8C) + (3 × %16C) (Sterken et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A Gene Ontology (GO) analysis of the 137 genes identified in our integrative eQTL, QTT and GWAS analysis indicated that cell‐cycle‐related processes were enriched among our putative kernel length‐related genes ( P = 2.0E‐4; Figure S3). The top‐ranked kernel‐related transcript (from the QTT analysis) was GRMZM2G099074; the closest homolog (55% identity of protein sequences; E = 3.0E‐118) to this gene in Arabidopsis is embryo defective 1379 ( AtEMB1379 or AtNSE1 , AT5G21140), a gene with established functions in regulating the cell cycle at the G2/M stage and in endo‐reduplication (Li et al ., ). The correlation between the expression of GRMZM2G099074 and kernel length was high (Spearman's ρ = 0.38, P < 3.5E‐12; Figure c).…”
Section: Resultsmentioning
confidence: 97%